Citizenship and the State. Obligatory Military Service in Contemporary Bolivia - Marta Cabezas Fernández (Íconos)
This article examines an institution which is central to sustaining racist, classist and patriarchal differentiated citizenship in Bolivia: obligatory military service. Through an analysis of the parliamentary debates that took place throughout 2008, during the first term in office of the governing Movement Towards Socialism (MAS) party, this research reveals the effectiveness of the state legislation mandating obligatory military service in legitimizing and naturalizing processes of domination.